2020
DOI: 10.15507/2078-9823.050.020.202002.174-189
|View full text |Cite
|
Sign up to set email alerts
|

To the Question of the Formation of the Spiritual and Moral Foundations of Russian Civil Identity

Abstract: Introduction. The priority for the development of Russian society is the strengthening of Russian statehood. The strategic purpose defining the policy of successful functioning and development of the state becomes the preservation of the Russian people as a single holistic entity. The main condition for achieving the unification of multi-ethnic and multi-religious Russian society is the formation of Russian identity. At the same time, there is a need to solve the discussion question of the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It has been also observed that basic mental patterns of one's world considered as objective and peculiarities of patterns functioning are often defined by economic relations, religious affiliation (Р. Bourdieu [11]) and characteristics of social group (А. Kleinman [12]). Mental patterns predetermine comprehension of what is right, natural and accessible in life.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also observed that basic mental patterns of one's world considered as objective and peculiarities of patterns functioning are often defined by economic relations, religious affiliation (Р. Bourdieu [11]) and characteristics of social group (А. Kleinman [12]). Mental patterns predetermine comprehension of what is right, natural and accessible in life.…”
Section: Discussionmentioning
confidence: 99%